2003
DOI: 10.1590/s0034-89102003000300019
|View full text |Cite
|
Sign up to set email alerts
|

Aedes albopictus may not be vector of dengue virus in human epidemics in Brazil

Abstract: Over 60,500 dengue cases were reported in the state of Espírito Santo (ES), Brazil, between 1995 and1998. The study's purpose was to identify whether Aedes albopictus was transmitting the dengue virus during an epidemic in the locality of Vila Bethânia (Viana County),Vitória, ES. From April 3 to 9, 1998, blood and serum samples were collected daily for virus isolation and serological testing. Four autochthonous cases were confirmed through DEN 1 virus isolation and two autochthonous cases through MAC ELISA te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0
6

Year Published

2003
2003
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 1 publication
1
10
0
6
Order By: Relevance
“…En el caso de los virus del dengue, A. albopictus es un vector menos competente y aún no se ha incriminado en su transmisión en Latinoamérica (3,(71)(72)(73)(74)(75). Sin embargo, la infección natural con DENV-1 y DENV-2 se ha comprobado en Buenaventura, Colombia, (11) y con DENV-2 y DENV-3, en México (12).…”
Section: Discussionunclassified
“…En el caso de los virus del dengue, A. albopictus es un vector menos competente y aún no se ha incriminado en su transmisión en Latinoamérica (3,(71)(72)(73)(74)(75). Sin embargo, la infección natural con DENV-1 y DENV-2 se ha comprobado en Buenaventura, Colombia, (11) y con DENV-2 y DENV-3, en México (12).…”
Section: Discussionunclassified
“…albopictus in Argentina certainly implies a risk to human health due to its potential to act as a bridge vector between rural and urban DF and YF, and also for other arboviruses as West Nile (Gratz 2004). In America, it was never implicated in dengue transmission and a study performed in Brazil (Degallier et al 2003) suggested that it still cannot be considered an inter-human dengue vector. However, it was found naturally infected with dengue virus in Brazil (Serufo et al 1993) and in Mexico (Ibañez-Bernal et al 1997).…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…In Brazil, Ae. albopictus does not seem to be an important vector of DENV (70) , but its role as vector of CHIKV and other arboviruses in Brazil needs to be more thoroughly studied.…”
Section: Vectorial Role Of Aedes (Stegomyia) Mosquitoesmentioning
confidence: 99%